2007
DOI: 10.1021/jp0768468
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Field Emission Properties of Double-Walled Carbon Nanotubes Synthesized by Hydrogen Arc Discharge

Abstract: We have synthesized high-purity double-walled carbon nanotubes (DWCNTs) by an arc-discharge method in hydrogen ambient. The DWCNTs were synthesized using a mixture of Fe catalyst and FeS promoter. Without FeS promoter, we only obtained single-walled carbon nanotubes (SWCNTs). The synthesized DWCNTs had outer diameters in the range of 3.0−3.4 nm and an average interlayer distance of 0.38 nm between graphene layers. The FeS promoter played a key role for the DWCNT growth. The DWCNTs indicated high electronic den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 48 publications
2
28
1
Order By: Relevance
“…The strong dependence observed between the presence of sulfur and the growth of DWCNTs was attributed to modification of the kinetics rather than energetics, since the growth of DWCNTs is supposed to be energetically more costly. Recently, Ha et al [4] confirmed the results obtained by Ci and co-workers: [3] DWCNTs were obtained if Fe was used as catalyst and FeS as promoter, but only SWCNTs were produced when FeS was absent. Neither investigation [3,4] reported the presence of sulfur atoms in the CNT walls.…”
Section: Introductionsupporting
confidence: 63%
“…The strong dependence observed between the presence of sulfur and the growth of DWCNTs was attributed to modification of the kinetics rather than energetics, since the growth of DWCNTs is supposed to be energetically more costly. Recently, Ha et al [4] confirmed the results obtained by Ci and co-workers: [3] DWCNTs were obtained if Fe was used as catalyst and FeS as promoter, but only SWCNTs were produced when FeS was absent. Neither investigation [3,4] reported the presence of sulfur atoms in the CNT walls.…”
Section: Introductionsupporting
confidence: 63%
“…4, the DWCNT field emitters showed a slight degradation after 25 hrs, indicating a very stable field emission. Compared with the previously reported emission stability of the SWCNTs, the emission stability of the DWCNTs was much better than that of the SWCNTs [30]. We believe that the stable emission properties were caused by two graphene layers and good crystallinity.…”
Section: ⅰ Introductioncontrasting
confidence: 62%
“…In fact, this turn-on field was a little lower than that of arc-SWCNTs [35]. Recently, there have been some reports on the field emission properties of the DWCNTs.…”
Section: ⅰ Introductionmentioning
confidence: 84%
“…The E to value of graphene films is also lower than that of free-standing sub-nanometer graphite sheets (E to, 4.7 V mm À1 ) synthesized by PECVD, [19] and the E to and E thr values are well comparable to those of CNT films fabricated by EPD (E to , 1.4-3.0 V mm À1 ) [28,29,40,41] and screen-printing (E to , 2-6.4 V mm À1 ) techniques. [42] The Fowler-Nordheim (F-N) theory is the most-commonly used model for understanding the electron emission from a metal surface under a strong applied field, and it has been also widely used to investigate the electron-emission behavior of various nanostructures, such as CNTs, [3][4][5][43][44][45] nanowires, [46] and nanowalls. [47] To elucidate the electron-emission mechanism and the differences in the field-emission behaviors of graphene-powder coating and graphene film, we plotted ln (J/E 2 ) versus 1/E, which yields a line, in good agreement with the F-N equation (Fig.…”
mentioning
confidence: 99%